Drivers of transformation of the maize sector in Nigeria - Assfaw Wossen, T.; Menkir, A.; Alene, A.; Abdoulaye, T.; Ajala, S.; Badu-Apraku, B.; Gedil, M.; Mengesha Abera, W.; Meseka, S.K. (Elsevier, 2023)
Maize is widely used for food, animal feed, and industrial raw material in Nigeria. This paper documents the important changes that characterize Nigeria’s maize production and area expansion along with contributing factors that have transformed maize from a backyard food crop to a dominant food security and commercial crop. Using both secondary and primary data on maize production and varietal adoption over the last six decades, we found that Nigeria now produces ten times more maize than it did in 1960 and four times more maize than it did in 2005. Our findings further suggested that government policies and institutional arrangements that promoted access to and use of modern inputs and increased demand of maize grain for food, feed, and other industrial uses have played major roles in transforming maize from a backyard crop to a dominant staple and commercial crop in Nigeria. Considering the impeding climate change threats to food security in Nigeria, policy interventions should be tailored towards further scaling-up of stress resilient and climate-smart maize varieties to improve the productivity, income, and resilience of smallholder farmers. This requires strong support not only to get recently released superior improved varieties into the hands of smallholder farmers but also to accelerate varietal turnover.